Management for development collection of papers - Sarabhai Vikram; Chowdhry Kamla (Delhi Indian Council of Social Science Research, 2004)
This volume contains selected papers dealing with several apects of management related to the tasks of government. These papers originally given as speeches & addresses, are brought together here for the 1st time. There are 3 convocation addresses- to th
Introduction by J R D Tata
Keywords: Scientific research; Vikram Sarabhai